FIRST RECORD OF INGESTION OF MICROPLASTICS BY A COMMERCIALLY IMPORTANT FISH IN THE CITY OF IQUITOS, PERUVIAN AMAZON - CHOTA-MACUYAMA, Werner (2020)
This study reports for the first time the microplastics ingestion in a important commercial fish in the Peruvian Amazon, recorded in individuals from the Belén market in the city of Iquitos, Loreto region, Peru. Of the eleven species analyzed (50 individuals), only in six individuals of boquichico Prochilodus nigricans Agassiz, 1829 were recorded 17 microplastic particles with an average (and standard deviation) of 0.34 (± 1.19) microplastics per individual. The frequency of occurrence of microplastic particles for the 50 individuals was 12%, and for P. nigricans was 46.2%. The sizes ranged from 0.40 to 4.39 mm and the shapes found were filaments (14 microplastics) and irregular fragments (3 microplastics). In the colors, blue was present in greater numbers (10 microplastics), followed by red (5 microplastics), green (1 microplastic) and light blue (1 microplastic). The results would be suggesting that some fishing areas are being affected by the mismanagement of plastic waste; negatively impacting the ecosystems and the ichthyofauna of the Peruvian Amazon, and through consumption could affect people's health.